What is the answer?

enter image source here

2 Answers
Dec 16, 2017

The first one.

Explanation:

When you divide by a fraction, you need to switch the sign to multiply and switch the fraction over. Then you can eliminate the similar factors which is (x+2)(x-3) leaving behind the answer which is 1.

Dec 16, 2017

5/(x+4)

Explanation:

This is an interesting problem

We must consider:

((f(x) / g(x)) ) / (((h(x)) / (u(x)) ) = (f(x) / (g(x) )) * (1 / ( (h(x))/(u(x)) ))

=> ( f(x)/(g(x) )) * ( (u(x))/(h(x) ))

So hence our problem becomes:

=> ((x+2)(x-3) )/ (x+4) * 5 / ((x+2)(x-3)

Using our algebra knowledge:

=> (cancel((x+2)(x-3)) )/ (x+4) * 5 / (cancel((x+2)(x-3))

=> 5/(x+4)